IMPACT OF TELEMEDICINE ON IMPROVING THE EFFECTIVENESS OF THE FIGHT AGAINST COVID-19: INNOVATIONS AND PROSPECTS - Baksheev, Andrei; Turchina, Zhanna; Galaktionova, Marina; Chesnokova, Larisa; Sharova, Olga; Rakhinskiy, Dmitriy (Revista Inclusiones, 2020)
The aim of this study is to analyze the possibilities of telemedicine as an innovative treatment method in the fight against coronavirus. The article analyzes telemedicine as a direction of medicine, medical service and a method of providing medical services. Based on an expert survey, the main tasks and functions of telemedicine are identified and the main types of telemedicine services in the fight against coronavirus are characterized. It has been proven that to overcome the negative consequences of the coronavirus pandemic and given the level of development of telemedicine in general, the availability of appropriate equipment and personal safety in the context of the coronavirus epidemic, the most promising areas of telemedicine use are patient counseling, telemedicine consultation and telemonitoring.